Biophysical and morphological attributes of semen after testicular degeneration - ANTOINE, D; PATTABIRAMAN, S R (The Indian Journal of Animal Reproduction, 2023)
Tellicherry bucks aged three years were subjected to scrotal insulation for 48 hours . The mean data of two semen collection of six bucks by artificial vagina taken in a week for three pre and 13 post-treatment were grouped and analysed statistically. The epididymal sperm are affected by scrotal insulation. There was characteristic time bound reversible changes in morphology of spermatozoa. Maximum damage was recorded on third week and complete recovery by tenth week of scrotal insulation.